Hubungan Antara Diabetes Melitus Tipe 2, Kadar High Density Lipoprotein dan Kadar Low Density Lipoprotein dengan Tipe Stroke di Rumah Sakit Umum Daerah Praya - Baiq Shareny Aprina Putri; Rohmania Setiarini; Fahriana Azmi; I Wayan Tunjung (Universitas Malahayati Lampung, 2025)
ABSTRACT Stroke is still one of the major health problems, not only in Indonesia but in the world. Stroke is the second leading cause of disability and death in the world. This study aims to analyze the relationship between type 2 diabetes mellitus (DM), high density lipoprotein (HDL) levels, and low density lipoprotein (LDL) levels with stroke type at Praya Regional General Hospital. This study used analytic observational method with cross-sectional design. The population was stroke patients who were hospitalized. The sampling technique was purposive sampling. The sample consisted of 91 respondents who met the inclusion and exclusion criteria. Data analysis was performed using the chi-square test. The results showed there was no significant relationship between type 2 diabetes mellitus and stroke type with a p-value of 0.684 (p-value ≥ 0.05). There is a significant relationship between HDL levels and stroke type with a p-value of 0.005 (p-value 0.05). There is a significant relationship between LDL levels and non-hemorrhagic stroke type with a p-value of 0.031 (p-value 0.05). In conclusion, there was no significant association between type 2 diabetes mellitus and stroke type, but there was a significant association between high density lipoprotein and low density lipoprotein levels with stroke type in Praya Regional General Hospital. Keywords: Stroke, Type 2 DM, HDL, LDL ABSTRAK Stroke masih menjadi salah satu masalah utama kesehatan, bukan hanya di Indonesia namun di dunia. Stroke menjadi penyebab utama kecacatan dan penyebab kematian nomor dua di dunia. Penelitian ini bertujuan untuk menganalisis hubungan antara diabtes melitus (DM) tipe 2, kadar high density lipoprotein (HDL), dan kadar low density lipoprotein (LDL) dengan tipa stroke di Rumah Sakit Umum Daerah Praya. Penelitian ini menggunakan metode observasional analitik dengan desain cross-sectional. Populasi adalah penderita penyakit stroke yang rawat inap. Teknik pengambilan sampel yaitu purposive sampling. Sampel terdiri dari 91 responden yang memenuhi kriteria inklusi dan eksklusi. Analisis data dilakukan menggunakan uji chi-square. Hasil penelitian menunjukkan tidak terdapat hubungan yang signifikan antara diabetes melitus tipe 2 dengan tipe stroke dengan p-value 0,684 (p-value ≥ 0,05). Terdapat hubungan yang signifikan antara kadar HDL dengan tipe stroke dengan p-value 0,005 (p-value 0,05). Terdapat hubungan yang signifikan antara kadar LDL dengan tipe stroke non hemoragik dengan p-value 0,031 (p-value 0,05). Kesimpulannya tidak ditemukan hubungan signifikan antara diabetes melitus tipe 2 dengan tipe stroke, tetapi terdapat hubungan signifikan antara kadar high density lipoprotein dan low density lipoprotein dengan dengan tipe stroke di Rumah Sakit Umum Daerah Praya. Kata Kunci: Stroke, DM Tipe 2, HDL, LDL